2020
DOI: 10.3390/nano10071390
|View full text |Cite
|
Sign up to set email alerts
|

Surface Stabilization Affects Toxicity of Silver Nanoparticles in Human Peripheral Blood Mononuclear Cells

Abstract: Silver nanoparticles (AgNPs) are one of the most investigated metal-based nanomaterials. Their biocidal activity boosted their application in both diagnostic and therapeutic medical systems. It is therefore crucial to provide sound evidences for human-related safety of AgNPs. This study aimed to enhance scientific knowledge with regard to biomedical safety of AgNPs by investigating how their different surface properties affect human immune system. Methods: preparation, characterization and stability evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…Cell-associated Ag (operationally defined as internalized or strongly bound) in PBMCs after 24 h of exposure to PVP-AgNPs and dissolved Ag was measured using ICP-MS after washing. For both AgNP and Ag ion exposure, the amount of Ag that was taken up by cells increased as the Ag concentration increased, which is expected and consistent with previous literature [ 49 50 ]. There was a significant difference between Ag that was detected in the cells (or bound strongly to the cells) after AgNO 3 treatment compared to NP treatment at concentrations of 500 and 1000 µg·L −1 , which is consistent with findings from previous studies [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Cell-associated Ag (operationally defined as internalized or strongly bound) in PBMCs after 24 h of exposure to PVP-AgNPs and dissolved Ag was measured using ICP-MS after washing. For both AgNP and Ag ion exposure, the amount of Ag that was taken up by cells increased as the Ag concentration increased, which is expected and consistent with previous literature [ 49 50 ]. There was a significant difference between Ag that was detected in the cells (or bound strongly to the cells) after AgNO 3 treatment compared to NP treatment at concentrations of 500 and 1000 µg·L −1 , which is consistent with findings from previous studies [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The modulation of the immune response by AgNPs is a unique area of interest because uncontrolled immune stimulation or immune suppression could lead to allergic reactions or reduce the body’s immune response to damage, infection, and cancers [ 5 ]. Currently, AgNPs have been reported to alter the morphology and viability of freshly isolated human peripheral blood mononuclear cells (hPBMCs) [ 6 ]. Moreover, pregnant mice exposed to AgNPs exhibited immunological dysfunction in the dam and placenta [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many lines of evidence have pointed out that AgNPs can induce apoptosis via extrinsic and intrinsic pathways and also act as a potent activator of autophagy [2,3,24,59]. In general, smaller-sized or positively charged AgNPs are acknowledged to possess more potent apoptosis-and autophagy-inducing activities than those with bigger dimensions or negative charges [14,60,61,62]. Nonetheless, this is not always the case.…”
Section: Discussionmentioning
confidence: 99%
“…Citrate-mediated stabilization renders negative charges to AgNPs surface, while cysteaminestabilized AgNPs surface appears to be positively charged. In actual fact, differential surface charging attributed to the choice of coating agents has been shown to dictate the modalities of cell death evoked by various ENMs, inclusive of AgNPs [13,14]. Although the majority of documents have suggested that positively charged AgNPs are more toxic towards eukaryotic cells than negatively charged AgNPs, some con icting in vivo evidence exists [15,16].…”
Section: Introductionmentioning
confidence: 99%